2015
DOI: 10.1039/c5ra08307a
|View full text |Cite
|
Sign up to set email alerts
|

Simple descriptors for assessing the outcome of aza-Diels–Alder reactions

Abstract: The iminium aza-Diels-Alder (iADA) reaction of cyclopentadiene with 16 protonated alkyl alkylimineglyoxilates was studied using density functional theory (DFT) in order to elucidate how different substitution patterns in the dienophile may affect the reaction's outcome. Additionally, the application of the polarisable continuum model (PCM) together with the evaluation of the thermodynamic properties at different temperatures further allowed the surveying of the importance of such factors. These effects were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…At the same time, νC (1) N (2) only accounts for 6.0% of ξ TS , on average. These results are in good accordance with the previous observations that this category ADA reactions are concerted, asynchronous cycloadditions. , …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…At the same time, νC (1) N (2) only accounts for 6.0% of ξ TS , on average. These results are in good accordance with the previous observations that this category ADA reactions are concerted, asynchronous cycloadditions. , …”
Section: Resultssupporting
confidence: 93%
“…The fourth and fifth study cases under reported in this work explored the application of VMARD as a way to characterize the motion along the reaction coordinate of the oxygen-transfer step in vanadium-catalyzed epoxidations, and also on different aza-Diels–Alder condensations. Both these studies relied on the data generated in previous studies by the authors. , …”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many similar correlations can be found using Tables – and Figure , which are left as an exercise for an interested reader. Alternative descriptors can also be systematically tested, for instance, Taft’s polar and steric substituent constants, as exemplified in the recent study of aza-Diels–Alder reactions …”
Section: Resultsmentioning
confidence: 99%
“…Alternative descriptors can also be systematically tested, for instance, Taft's polar and steric substituent constants, as exemplified in the recent study of aza-Diels−Alder reactions. 44 ■ CONCLUDING REMARKS Thermodynamics of fluorination, chlorination, and bromination is reported and discussed. It was found that halogenation of the N-ethyl-N-methylpyrrolidinium, N-ethylpyrrolidinium, and protonated pyrrolidine cations is thermodynamically allowed in almost all cases.…”
Section: ■ Results and Discussionmentioning
confidence: 99%